Differential behavior to drought of two elite potato cultivars grown in southeastern pampean region of Argentina - Tagliotti, Martín Enrique; Giuliano, Sergio; Puricelli, Marino Marcelo; Zambelli, Andrés; Bedogni, Maria Cecilia (Indian Council of Agricultural Research, 2024)
Potatoes production requires large inputs of water for which development of drought tolerant cultivars is particularly relevant to ensure or even increase its productivity. Two elite cultivars, Newen INTA and Spunta, were evaluated in the field under contrasting water regimes. After drought treatment, the yield of marketable tubers decreased 53% in Spunta and 22% in Newen INTA while the number of marketable tubers decreased 32% in both cultivars. Yield of tuber > 90 mm only decreased in Spunta (62.81%, p < 0.05). Newen INTA showed a greater reduction in the shoot and root dry biomass than Spunta, while the root/shoot ratio was higher in Newen INTA. Proline content increased 61% in both cultivars under drought treatment. Drought tolerance indices (GMP and DTI) were higher in Newen INTA, and the drought susceptibility index was higher in Spunta. Proline content was correlated with root dry biomass and the marketable tuber number in both cultivars. Dry root biomass correlated with the yield of marketable tubers and the number of marketabletubers. In drought conditions, Newen INTA showed greater tolerance to drought. Therefore, Newen INTA emerges as a useful genotype to contribute to increasing crop productivity in areas subject to water stress.